Abundância e sucessão de Palythoa caribaeorum (Duchassaing e Michelotti, 1860): um estudo experimental no banco dos Abrolhos, BA - Basílio, Patrícia Silva (2013)
Coral reefs are recognized as the largest biological structures in the oceans. They formed by building organisms (e.g. scleractinian corals and calcareous algae). In the last five decades, there have been declines in coral cover worldwide. Overfishing, pollution and increased coastal sedimentation are pointed as the main impacts responsible for declines in abundance of reef-building organisms and increases in abundance of non-building ones (e.g. algae), a process known as "phase shift". The zoanthid Palythoa caribaeorum is abundant in the Atlantic, particularly in Brazil. It is able to tolerate high environmental variability and displays the highest growth rate among all Anthozoans. Moreover, it has elaborated strategies of competition for space, which makes it competitively superior to most other benthic invertebrates. The present work was performed in the Abrolhos Bank, Bahia, with the following main objectives: 1) to describe the spatio-temporal patterns in cover of P. caribaeorum across the Abrolhos Bank, 2) evaluate the relative influence of distance offshore, depth, latitude and biomass of fish zoanthid predators in the abundance of P. caribaeorum; 3) describe the benthic succession in two areas in which P. caribaeorum was excluded (one next to the coast and subject to high sedimentation levels and another far from the coast and subject to low sedimentation). The study of spatio-temporal patterns was conducted in six reefs from 2006 to 2008: Parcel dos Abrolhos (five sites), Archipelago (five sites), Timbebas (three sites), Itacolomis (eight sites), Parcel das Paredes (two sites) and Sebastião Gomes (one site). The exclusion experiment was conducted from 2006 to 2009 in the top of the reefs of sites Arenguera (Parcel das Paredes) and PAB4 (Parcel dos Abrolhos). Four 5 x 5 m areas were selected at each site. Two of them were manipulataded (all P. caribaeorum removed) and the other two were not manipulated (control). Three treatments were applied within each area: 1) closed cage, to exclude reef fish known to predate P. caribaeorum, 2) open cage (control for the effect of the cage), 3) without cage. The methods used were photo-quadrats (benthic assessments) and stationary visual census (fish assessments). The results showed that P. caribaeorum dominates the top of the reefs, with insignificant coverage in the wall. This suggests the preference of P. caribaeorum for horizontal inclination and high light levels. The relative cover of P. caribaeorum was higher in the sites PAB4, PAB5, TIM2, TIM3, ARENG and SG, and was positively influenced by depth and negatively influenced by distance offshore. The five most abundant reef fish species recognized as predatos of zoanthids in terms of biomass were A. saxatilis, P. paru, P. arcuatus, H. ciliares, and C. striatus. In the exclusion experiment, a slow recovery of P. caribaeorum was recorded in the manipulated areas, with no differences in recolonization rates between the two sites (near or away from the coast). Settlement of P.caribaeorum at the manipulated areas may have been inhibited by the proliferation iof fast growing epilithic algae, particularly inside closed cages. The overall average growth rate was higher in ARENG (0.23 cm-2.day-1) than in PAB4 (0.12 cm-2.day-1) in the manipulated area. However, in the control area of PAB4 P. caribaeorum showed a growth rate of 3.18 cm-2.day-1, while in the control area of ARENG it declined (-0.25 cm-2.day-1). Total coverage of P. caribaeorum declined in the control area of ARENG due to a bleaching event that occurred throughout the study. Conclude that: 1) environmental variables such as depth and distance from the coast, are more important than biotic (eg predation) in the dynamics of P. caribaeorum, 2) despite the coverage of P. caribaeorum present negative relationship with distance from the coast, recolonization rates were not higher at the site closest to shore, 3) coverage of P. caribaeorum increases in periods near the summer at both sites, and 3) low density of Palythoa was unfavorable for a faster process of recolonization.